Digital Da’wah: Effective Strategies in Spreading Islam through Social Media - Abdul Chalim; St. Rahmah; Randi Rudiana; Jasafat Jasafat (Journal of Noesantara Islamic Studies, 2025)
The rise of social media has revolutionized communication and presented new opportunities for Islamic propagation (da’wah). As digital platforms become integral to modern life, they offer unprecedented potential for disseminating Islamic teachings to a global audience. However, the effectiveness of digital da’wah depends on strategic engagement, content quality, and adaptability to diverse audiences. This study aims to explore effective strategies for spreading Islam through social media, identifying key factors that influence reach, engagement, and impact. A mixed-methods approach was employed, combining content analysis of 200 da’wah-related posts across major social media platforms with surveys and interviews of 150 Islamic content creators and their audiences. Quantitative data measured engagement metrics, while qualitative insights explored perceptions of effectiveness and challenges faced by content creators. The findings indicate that successful digital da’wah strategies prioritize authenticity, audience interactivity, and relevance to contemporary issues. Visual storytelling, short video formats, and consistent posting schedules were identified as highly effective tactics. Challenges such as combating misinformation and addressing audience diversity were also highlighted. The study concludes that social media can be a powerful tool for Islamic propagation if utilized with strategic planning and cultural sensitivity. Future efforts should focus on capacity-building for content creators and fostering collaborative networks.